Intratumoral heterogeneity of macrophages and fibroblasts in breast cancer is associated with the morphological diversity of tumor cells and contributes to lymph node metastasis - Tashireva, Lubov A.; Kzhyshkowska, Julia (Immunobiology, 2017)
Recent studies have highlighted the heterogeneity of the tumor microenvironment (ME) and the importance of its analysis to the understanding of its impact on clinical outcomes. In this study, we aimed to analyze the intratumoral distribution of macrophages and fibroblasts in breast cancer (BC) based on the morphological diversity of tumor cells (tubular, alveolar, solid, trabecular and discrete structures) and the clinicopathological parameters of the disease. Thirty-six patients with invasive breast carcinoma of no special type were included in the study. The distribution of macrophages and fibroblasts in the MEs of different morphological structures was assessed using laser microdissection-assisted quantitative RT-PCR analysis of marker genes and double immunofluorescence staining for the CD68, RS1, aSMA, and FAP proteins. Gene expression microarrays were used to determine the expression of genes involved in the regulation of macrophage and fibroblast phenotypes in different morphological structures. We found that different macrophage and fibroblast subpopulations were simultaneously observed in the MEs of morphologically distinct structures but that the frequency of their detection and number of cells detected varied significantly among these structures. In particular, macrophages and fibroblasts were more frequently detected in the ME of solid structures and were rarely observed in tubular structures. A high number of CD68+RS1+ macrophages in the ME of solid structures was found to be associated with an increased frequency of lymph node metastasis in luminal B HER2− BC. In contrast, in luminal B HER2+ BC, lymph node involvement was related to the high representation of aSMA+FAP+ fibroblasts around trabecular structures. Morphologically distinct structures differed in the mechanisms regulating the macrophage and fibroblast phenotypes. The highest number of overexpressed genes controlling macrophage and fibroblast functions was observed in discrete groups of tumor cells, and the lowest number was observed in alveolar and solid structures. Taken together, our findings indicate the heterogeneous distribution of macrophages and fibroblasts in breast tumors and its close relation to the intratumoral morphological diversity of BC and contribution to lymph node metastasis.